The Effect Of Complaint Handling And Service Quality On Customer Satisfaction Of Maju Matan Printing In Surabaya - Wahyu Darmawan; Damajanti Sri Lestari; Moch. Arfani; Liling Listyawati (International journal of technology and education research, 2025)
This research is directed to explore how managing customer complaints and the quality of services provided can shape the level of consumer satisfaction at the Maju Mapan Surabaya Printing House. The approach taken is quantitative, with all printing customers being the coverage of the population, then filtered into This study involves 96 individuals who were selected not at random, but through a purposive sampling process according to the criteria that have been determined by the researcher. Data collection was carried out through a Likert scale questionnaire, then processed using multiple linear regression analysis, complete with By applying validity, reliability, and classical assumption tests as the initial gateway for data processing, it was revealed that complaint management reflects a real influence on customer satisfaction, as well as service quality. If both are tested together, the effect remains significant with an Adjusted R² value of 0.601. This means that 60.1% of changes in customer satisfaction are influenced by these two factors, while another 39.9% come from the influence of external factors that are not accommodated in the scope of this study. This conclusion confirms that prompt response to complaints and quality service are strategic keys in maintaining consumer satisfaction in the printing sector.